2012
DOI: 10.1155/2012/282131
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Chinese Traditional Exercise Baduanjin Modulating the Blood Lipid Metabolism

Abstract: Background. Baduanjin exercise is considered to be beneficial to modulate the blood lipid metabolism. The purpose of the systematic review was to assess the potential efficacy and safety of Baduanjin exercise. Methods. MEDLINE, EMBASE, CBM, CNKI, VIP, Chinese Important Conference Papers Database, and Chinese Dissertation Database were searched for all prospective-controlled trials of Baduanjin exercise from their inception to December 31, 2011. Results. A total of 14 studies were included. Comparing with no tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 10 publications
0
64
1
Order By: Relevance
“…Ba Duan Jin has been shown to enhance sleep quality in older adults (Chen, Liu, Huang, & Chiou, 2012), as well as alleviate symptoms of knee osteoarthritis . Systematic reviews have shown Ba Duan Jin can decrease plasma total cholesterol, triglycerides, and low-density lipoprotein-C levels and increase plasma highdensity lipoprotein-C levels (Mei et al, 2012). However, there is currently insufficient evidence to support Ba Duan Jin as an exercise to improve the balance ability of older adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ba Duan Jin has been shown to enhance sleep quality in older adults (Chen, Liu, Huang, & Chiou, 2012), as well as alleviate symptoms of knee osteoarthritis . Systematic reviews have shown Ba Duan Jin can decrease plasma total cholesterol, triglycerides, and low-density lipoprotein-C levels and increase plasma highdensity lipoprotein-C levels (Mei et al, 2012). However, there is currently insufficient evidence to support Ba Duan Jin as an exercise to improve the balance ability of older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The slow, gentle, graceful movements of Ba Duan Jin, combined with meditation, deep breathing, and relaxation, move Qi throughout the body. Current studies have suggested that Ba Duan Jin training appears to have substantive benefits for older adults with physical and mental disorders, such as anxiety, depression, hyperlipidemia, spinal problems, osteoarthrosis, and type 2 diabetes (An et al, 2013;Hsu, Wang, Liu, & Liu, 2008;Mei, Chen, Ge, Zheng, & Chen, 2012). Ba Duan Jin has several health effects, and the levels of exercise intensity and simplicity of movements make it suitable for practice among older adults.…”
mentioning
confidence: 99%
“…Unlike Tai Chi, Baduanjin exercise is characterized by simple, slow, relaxing movements, which is composed of 8 set of actions including support heaven with both hands, dragon sprays water with force, big bird spreads its wings, lift window to look at the moon on the left, descend to earth with force, beautiful maiden twists her waist to the right, extend shoulders to bring hands together, and dragon claws to the left [9]. In China, it has been widely practiced for the treatment of various conditions, including hyperlipidemia [12], ischemic stroke [13], sleep disturbances [14], knee osteoarthritis [15], bone loss [16], and oxidative stress [17], due to its promotion of good health [18], ease of learning, low physical demand [19], and gentle nature compared to intense exercise [20]. Furthermore, the Chinese Health Qigong Association recommends Baduanjin for generalized application in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Practising Baduanjin results in physiological benefits (Jing et al, 2013;Mei et al, 2012) for automatic nerves (Wu and Hu, 2013), osteoarthritis , strokes and bone loss prevention (Chen et al, 2006), is therefore recommended for the elderly . Studies also report enhancements in psychological health through practising this exercise (Liao, 2009;Wang, 2013;Wu, 2012), such as improvements in suboptimal health (Geng and Wang, 2008;Jiang et al, 2010) and emotional regulation for detention centre officers (He et al, 2009), proposing the amelioration of mental health (Han, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies also report enhancements in psychological health through practising this exercise (Liao, 2009;Wang, 2013;Wu, 2012), such as improvements in suboptimal health (Geng and Wang, 2008;Jiang et al, 2010) and emotional regulation for detention centre officers (He et al, 2009), proposing the amelioration of mental health (Han, 2013). One review investigated the physical effects of Baduanjin (Mei et al, 2012), but no reviews have analysed its effectiveness on psychological functionality. The current comprehensive review looks into the effects of Baduanjin on the mental health of healthy people and patients with chronic illnesses, involving a wide spectrum of age groups.…”
Section: Introductionmentioning
confidence: 99%